Perlindungan Hak Cipta dan Pertanggungjawaban Pihak Pelanggar terhadap Penyebaran Film Ilegal di Telegram - Rasyida Harahap, Syarifah Bilqis (Equality : Jurnal Hukum dan Keadilan, 2024)
With the advancement of time and technology, society has become increasingly dependent on social media, which offers various features to facilitate activities, including entertainment. One popular application used for entertainment is Telegram, which hosts numerous illegal films distributed by irresponsible individuals. This situation causes losses for filmmakers, who are entitled to moral and economic rights over their creations as stipulated in the Copyright Law (UUHC). This study aims to examine whether the distribution of illegal films violates economic rights under Article 9 (1) b of the UUHC and whether it can be categorized as piracy under Article 113 (4) of the UUHC. Furthermore, this research analyzes the mechanisms for copyright protection for filmmakers and the accountability of individuals distributing pirated films through civil and criminal lawsuits, which arise due to negligence in monitoring user activities in accordance with applicable regulations. The findings of this study indicate that the distribution of illegal films on Telegram infringes on the economic rights of filmmakers and is subject to sanctions under the UUHC. Legal protection of copyright can be pursued through legal actions, including civil and criminal lawsuits, against violators.